Penerapan Prinsip Desain Richard Rogers Di Pekanbaru Dalam Perancangan E-Sports Center - Bimantara Asnur; Yohannes Firzal; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The e-Sports center is motivated by the rapid development of e-Sports in Indonesia, including Pekanbaru, various events are held means that e-Sports high enthusiasts today. E-Sports has becomea sport that has formalized and fully supported by the government, as a promising sport for athletes in the future. However, with such rapid development, it is not followed by facilities that couldaccommodate the events, therefore the center of the e-Sports aims to meet all the needs of buildings and other facilities so that e-Sports are even better. In planning the e-Sports Center, it is based onRichard Roger’s design principles about